Lunar polar exploration mission for water prospection - JAXA's current status of joint study with ISRO. (November 2020) - Hoshino, Takeshi; Wakabayashi, Sachiko; Ohtake, Makiko; Karouji, Yuzuru; Hayashi, Takahiro; Morimoto, Hitoshi; Shiraishi, Hiroaki; Shimada, Takanobu; Hashimoto, Tatsuaki; Inoue, Hiroka; Hirasawa, Ryo; Shirasawa, Yoji; et al.
Abstract: Currently, several polar explorations of the Moon are planned, because it has been suggested that water ice might be present in the lunar polar region based on remote sensing observation of the lunar surface using a neutron spectrometer and visible to infrared spectrometer. However, the precise amount and state of the water ice are still unknown. At the Japan Aerospace Exploration Agency (JAXA), we are also studying exploration of the lunar surface for resources, especially cold-trapped volatile such as water ice using a rover. Volatile materials are expected to be useful for future human activity on the Moon and there is strong interest in the origin and concentration mechanism of the water ice. Additionally, the polar regions are among the best candidates for long-term activity because of their long sunlight duration. To realize the mission, we are currently developing various technologies peculiar to exploration of lunar polar regions. This paper details the present status of the Japanese Lunar Polar Exploration Mission. Highlights: Volatile materials are expected to be useful as resources for activity on the Moon. The Japan Aerospace Exploration Agency (JAXA) is studying on lunar polar mission. This is a joint study with the Indian Space Research Organisation (ISRO). ISRO and JAXA held the joint mission definition review in December 2018. JAXA is developing technologies peculiar to exploration of lunar polar regions.